(untitled) (International Journal of Engineering and Computer Science, 2014)
The conventional or the traditional way of collecting the toll from the vehicle owners or the drivers is to stop the car by the toll gate stations and then pay the amount to the toll collector in the toll booth, after which the gate is opened either mechanically or electronically for the driver to get through the toll station. So in order to stop all these problems and inconvenience, we introduce an automated way of collecting the toll and traffic management. It is called Electronic Toll Gate Stations using RFID Technology. In this paper we use ARM based LPC2148, PIC18F452, RF434, ZigBee and GSM. In this system three sub systems are present. Those are central database system, toll gate unit and vehicle unit. The vehicle unit consists of an active RF434, GSM modem, keypad and ignition control unit. The RF434 sends the necessary vehicle identification information to toll gate unit based on user request. GSM send the vehicle starting intimation to user and also receive the necessary command from user to stop the vehicle. Keypad is used for authentication password to access to start the vehicle. The toll gate unit contains the RF434 which reads the necessary vehicle identification information. When a vehicle comes in the vicinity of the toll gate the tag attached to the vehicle communicates with the toll gate station and the information of tag is sent to central data base station using ZigBee wireless communication protocol. At the other side the central data base system receives this information and compares from database for sufficient details and amount information. If the details are matched and sufficient amount is found then the successful information is sent to the corresponding toll gate station via ZigBee. At the toll gate if the received information is success then the toll gate will be opened for the vehicle to pass and the gate will be closed automatically based on IR sensor interfaced at toll gate